The genome sequence of Dyella jiangningensis FCAV SCS01 from a lignocellulose-decomposing microbial consortium metagenome reveals potential for biotechnological applications - Desiderato, Joana G. [UNESP]; Alvarenga, Danillo O. [UNESP]; Constancio, Milena T. L. [UNESP]; Alves, Lucia M. C. [UNESP]; Varani, Alessandro M. [UNESP] (FapUNIFESP (SciELO), 2018)
Cellulose and its associated polymers are structural components of the plant cell wall, constituting one of the major sources of carbon and energy in nature. The carbon cycle is dependent on cellulose-and lignin-decomposing microbial communities and their enzymatic systems acting as consortia. These microbial consortia are under constant exploration for their potential biotechnological use. Herein, we describe the characterization of the genome of Dyella jiangningensis FCAV SCS01, recovered from the metagenome of a lignocellulose-degrading microbial consortium, which was isolated from a sugarcane crop soil under mechanical harvesting and covered by decomposing straw. The 4.7 Mbp genome encodes 4,194 proteins, including 36 glycoside hydrolases (GH), supporting the hypothesis that this bacterium may contribute to lignocellulose decomposition. Comparative analysis among fully sequenced Dyella species indicate that the genome synteny is not conserved, and that D. jiangningensis FCAV SCS01 carries 372 unique genes, including an alpha-glucosidase and maltodextrin glucosidase coding genes, and other potential biomass degradation related genes. Additional genomic features, such as prophage-like, genomic islands and putative new biosynthetic clusters were also uncovered. Overall, D. jiangningensis FCAV SCS01 represents the first South American Dyella genome sequenced and shows an exclusive feature among its genus, related to biomass degradation.
Keywords: Comparative genomics; Genome annotation; Glycoside hydrolases; Plant cell wall polysaccharides; Rhodanobacteraceae